PENGARUH SHIFT DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DEPARTMENT STORE KOTA SUKABUMI - Eva Marsusanti (Universitas Bina Sarana Informatika Kota Sukabumi, 2015)
This research describes clearly about shift, work environment, and employee performance Matahari Department Store kota Sukabumi. The first objective is to examine the influence of shift to employee performance. The second objective is to examine the influence work environment to employee performance. The third objective is to examine the influence of shift and work environment through employee performance simultaneously. This research used descryptive anaysis methode. Partially, variable of service quality indicates the highest influence toward variable of customer satisfaction with R2 = 0,354. Simultaneously, the variables of service and product quality influence variable of customer satisfaction with adjusted R2 = 0,625.